영아교사의 정서지능이 놀이지원역량에 미치는 영향: 영아교사 민감성의 매개효과를 중심으로 - 김양희(Yanghee Kim); 김정민(Jungmin Kim) (가정과삶의질연구, 2024)
본 연구는 영아교사의 놀이지원역량이 가지는 중요성에 주목하여, 영아보육의 질을 결정하는 주요한 인적환경인 영아교사의 놀이지원역량에 영향을 미치는 변인들을 규명하는 것을 목적으로 하였다. 이를 위해 영아교사의 정서지능과 민감성이 놀이지원역량에 미치는영향을 살펴보고, 특히 영아교사의 정서지능과 놀이지원역량 간의 관계에서 민감성의 매개효과를 검증하고자 하였다. 연구대상은 대구⋅ 경북지역 어린이집에 근무 중인 영아반 보육교사 207명이며, 자기보고법(질문지)을 통해 교사의 놀이지원역량, 정서지능, 민감성을 측정하였다. 자료 분석을 위해 SPSS 26.0 프로그램을 활용하여 영아교사의 놀이지원역량, 정서지능, 민감성의 기술통계치 및 상관관계를 살펴본 후 SPSS Process Macro(v4.2)의 4번 모델을 활용하여 매개효과 유의성을 검증하였다. 주요 연구결과는 다음과 같다. 첫째, 영아교사의정서지능과 민감성, 놀이지원역량은 서로 유의미한 정적 관련성을 가지는 것으로 나타났다. 둘째, 영아교사의 정서지능이 놀이지원역량과 민감성에 미치는 영향은 모두 유의한 것으로 나타났다. 셋째, 영아교사의 정서지능은 민감성을 매개로 놀이지원역량에 유의미한 영향을 미치는 것으로 나타났다. 본 연구에서는 영아교사의 정서지능과 민감성이 놀이지원역량에 영향을 미치는 주요 요인이며, 정서지능과놀이지원역량 간의 관계에서 민감성이 매개변인으로서 역할을 함을 확인하였다. 이와 같은 결과는 영아교사의 놀이지원역량 향상을 위해교사의 정서지능과 민감성 증진을 위한 다양한 노력이 필요하며, 영아교사의 놀이지원역량 향상을 위한 교사교육 및 어린이집 지원 프로그램 개발⋅시행 시 놀이지원과 직접적으로 관련된 내용 뿐 아니라, 교사의 정서지능과 민감성 증진과 관련된 내용들이 함께 고려될필요가 있음을 시사한다. The purpose of this study was to examine the effect of emotional intelligence and sensitivity of infant teachers on play support competency, and to verify the mediating effect of sensitivity in the relationship between infant teachers’ emotional intelligence and play support competency. The subjects of this study were 207 infant teachers working at daycare centers in Daegu and Gyeongbuk. The study assessed teachers’ play support competence, emotional intelligence, and sensitivity using a questionnaire. For data analysis, SPSS 26.0 program was used to examine descriptive statistics and correlations among variables. The mediating effect was analyzed by SPSS Process Macro Model4(v4.2). The results of this study were as follows. First, it was found that the correlations among infant teachers’ emotional intelligence, sensitivity and play support competency were positively significant. Second, the effects of infant teachers’ emotional intelligence on play support competency and sensitivity were found to be significant. Third, it was found that the emotional intelligence of infant teachers had a significant effect on play support competency through sensitivity. In this study, it was confirmed that emotional intelligence and sensitivity of infant teachers are the main factors affecting the play support competency, and that sensitivity plays a role as a mediating variable in the relationship between emotional intelligence and play support competency. These results suggest that various efforts are needed to improve infant teachers’emotional intelligence and sensitivity in order to improve their play support competency. It also suggests that when developing and implementing teacher education and daycare center support programs to improve infant teachers’ play support competency, not only content directly related to play support, but also content related to infant teachers’ emotional intelligence and sensitivity needs to be considered. KCI Citation Count: 0